Creating the empress : politics and poetry in the age of Catherine II - Proskurina, V. I͡U (Ars Rossika., 2011)
In Creating the Empress, Vera Proskurina examines the interaction between power and poetry in creating the imperial image of Catherine the Great, providing a detailed analysis of a wide range of Russian literary works from this period, particularly the main Classical myths associated with Catherine (Amazon, Astraea, Pallas Athena, Felicitas, Fortune, etc.), as well as how these Classical subjects affirmed imperial ideology and the monarch's power. The book allows for the viewing of these themes and motifs not only in the immediate historical context of Catherine II's reign, but also in the context of the broader European symbolic traditions. Each chapter of the book revolves around the major events of Catherine's reign (as well as some major literary works) that give a broad framework to discuss the evolution of important recurring motifs and images. --From publisher's description.